Naxi ethnic group's seven-star sheepskin shawl: a semiotic analysis / Liu Chang, Mat Redhuan Samsudin and Zou Yuwen - Chang, Liu; Samsudin, Mat Redhuan; Yuwen, Zou (Faculty of Art and Design, 2024)
With the rapid development of economic globalisation, the process of modernisation has brought great challenges to the development of Chinese ethnic minority Naxi costumes while changing our lifestyles. Although the importance of traditional ethnic costumes as an important cultural heritage has attracted extensive attention from scholars at present, studies that explore traditional ethnic costumes in depth from a semiotic perspective are still relatively scarce. The seven-star sheepskin shawl is the most distinctive attire of the Naxi ethnic group. Beyond its practical functions of providing warmth and durability, as well as its decorative purpose, it encapsulates the rich historical and cultural significance of the Naxi people. This paper delves into the seven-star sheepskin shawl from a semiotic perspective, examining it at three levels: syntactics, semantics, and pragmatics. Morris's semiotics consists of three integral parts: syntactics, semantics, and pragmatics. Through the application of Morris's semiotic theory alongside case studies, this paper concludes that the Naxi seven-star shawl embodies stylistic art, cultural connotations, and functional categories. The objective of this paper is to deepen our comprehension of Naxi culture, aiding us in grasping the cultural significance concealed within the seven-star sheepskin shawl. Furthermore, it provides valuable insights and inspiration for contemporary dress design.